Microdosimetric studies of Auger electrons from DNA-incorporated 123-I using the micronucleus assay and the Geant4 Monte Carlo simulation tookit - Fourie, Hein (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.